Global Analysis of Height‐Resolved Ice Particle Categories From Spaceborne Lidar - Kaori Sato; Hajime Okamoto (Geophysical Research Letters)
Abstract A more accurate representation of ice‐phase processes in numerical models necessitates an enhanced understanding of ice‐particle microphysics and their respective formation conditions. Prior in situ measurements have noted distinctive ice‐particle shape characteristics associated with different cloud systems and geographical locations. The recent advancement in ice‐particle backscattering theories enables a more comprehensive exploration of the geographical distribution and seasonal dependence of ice‐particle shape categories than ever before. This exploration is being undertaken for the first time using space‐borne lidar measurements. Distinct geographical preferences were observed for five different ice‐particle categories. Bullets/rosettes were the most common, followed by Voronois, which were especially prevalent in high‐level tropical clouds, and 2D columns, which were commonly found in mid‐ and low‐level clouds. Droxtals were primarily observed in high‐level subtropical regions. The global distribution of ice‐particle types provides valuable insights into the physical processes related to ice cloud particle shape formation, cloud duration, and radiative impacts.